Comparative Profitability of Plant and Ratoon Methods of Sugarcane Cultivation in Kamareddy District of Telangana, India - , Vaishnavi Varala; , B. Sowjanya; , I. Shakuntala Devi; , P. Prashanth (Archives of Current Research International, 2025)
Aims: The study aimed to analyze and compare the cost of cultivation, profitability and farm income measures between fresh (plant) and ratoon sugarcane cultivation methods. Study Design: A comparative economic analysis was conducted using structured cost concepts and farm income indicators across both methods of sugarcane production. Place and Duration of Study: The study was conducted in Kamareddy district, Telangana, during the 2023–2024 cropping season. Methodology: Primary data were collected from a sample of 80 sugarcane farmers (40 plant crop and 40 ratoon sugarcane farmers) through personal interviews using a pre-tested schedule. The data was analyzed using cost concepts such as Cost A1, A2, B1, B2, C1, C2, and C3. Farm profitability was assessed through gross returns, net returns, cost of production per quintal, farm business income, family labour income, and farm investment income. Results: The total cost of cultivation was ₹2,57,936.66/ha for plant and ₹1,73,729.05/ha for ratoon sugarcane crop. Variable costs accounted for 93.4 per cent and 92.08 per cent of total costs respectively in plant and ratoon, where machine and human labour occupying major share. Cost concepts (A1 to C3) were consistently higher for plant cane. The Gross returns were also higher in plant sugarcane (₹3,57,102 /ha) than in ratoon cane (₹ 2,76,426/ha). However, ratoon sugarcane recorded a higher net income (₹1,02,696.94/ha), a lower cost of production (₹169.69/q), and a higher B:C ratio (1.59) when compared to plant cane, which had a net income of ₹99,165.33/ha, a higher cost of production (₹195.02/q), and a lower B:C ratio (1.38). Income indicators such as farm business income and family labour income were also slightly higher in ratoon cultivation. Conclusion: While plant sugarcane offers higher gross income due to superior yields, ratoon sugarcane provides better net returns, cost efficiency, and profitability. Thus, ratoon cropping is a more economically viable option under the studied production conditions.